Elmohardyia Rafael (Diptera, Pipunculidae) from northeastern Brazil: new records and description of new species - Marques, Dayse W.a.; Rafael, José A. (Zootaxa, 2015)
Eleven species of Elmohardyia are recorded for the first time in northeastern Brazil, the most arid Brazilian region. There are two new records, E. lindneri (Collin) and E. trinidadensis (Hardy), and nine new species, which are here described and illustrated: Elmohardyia cearensis sp. nov.; E. cheliformis sp. nov.; E. distincta sp. nov.; E. formosa sp. nov.; E. limeirai sp. nov.; E. martae sp. nov.; E. potiguar sp. nov.; E. quadricornis sp. nov. and E. rosalinae sp. nov.